New Insights into the Regulation of Cell-Surface Signaling Activity Acquired from a Mutagenesis Screen of the Pseudomonas putida IutY Sigma/Anti-Sigma Factor - Bastiaansen, Karlijn C.; Civantos, Cristina; Bitter, Wilbert; Llamas, María A. (Frontiers in Microbiology, 2017)
Cell-surface signaling (CSS) is a signal transfer system that allows Gram-negative bacteria to detect environmental signals and generate a cytosolic response. These systems are composed of an outer membrane receptor that senses the inducing signal, an extracytoplasmic function sigma factor (σECF) that targets the cytosolic response by modifying gene expression and a cytoplasmic membrane anti-sigma factor that keeps the σECF in an inactive state in the absence of the signal and transduces its presence from the outer membrane to the cytosol. Although CSS systems regulate bacterial processes as crucial as stress response, iron scavenging and virulence, the exact mechanisms that drive CSS are still not completely understood. Binding of the signal to the CSS receptor is known to trigger a signaling cascade that results in the regulated proteolysis of the anti-sigma factor and the activation of the σECF in the cytosol. This study was carried out to generate new insights in the proteolytic activation of CSS σECF. We performed a random mutagenesis screen of the unique IutY protein of Pseudomonas putida, a protein that combines a cytosolic σECF domain and a periplasmic anti-sigma factor domain in a single polypeptide. In response to the presence of an iron carrier, the siderophore aerobactin, in the extracellular medium, IutY is processed by two different proteases, Prc and RseP, which results in the release and activation of the σIutY domain. Our experiments show that all IutY mutant proteins that contain periplasmic residues depend on RseP for activation. In contrast, Prc is only required for mutant variants with a periplasmic domain longer than 50 amino acids, which indicates that the periplasmic region of IutY is trimmed down to ~50 amino acids creating the RseP substrate. Moreover, we have identified several conserved residues in the CSS anti-sigma factor family of which mutation leads to constitutive activation of their cognate σECF. These findings advance our knowledge on how CSS activity is regulated by the consecutive action of two proteases. Elucidation of the exact mechanism behind CSS activation will enable the development of strategies to block CSS in pathogenic bacteria.